COMPARISON OF THE EFFECTIVENESS OF FERACRYLUM 1% AND FERACRYLUM 4% IN STOPING BLOODING AFTER GINGIVA INCISION - Adilah Tsamarah; Erwid Fatchur Rahman; Rahmawati Sri Praptiningsih (Jurnal Medali, 2022)
Background: Bleeding is often found in dental practice. Excessive bleeding can hinder wound healing. For the surgeon to achieve rapid and effective hemostasis is important. Therefore, a topical hemocoagulation solution is given to help control surface bleeding by applying it locally. One such topical agent is Feracrylum. Feracrylum is a polymer of polyacrylic acid containing 0.05 to 0.5% iron. Feracrylum iron element will react with albumin and then convert water-soluble fibrinogen into water-insoluble fibrin which then forms a coagulum. This study aims to compare the effectiveness of Feracrylum 1% and Feracrylum 4% in stopping bleeding after gingival incision.Method: This study is a true experimental study that includes 3 treatment groups, namely the group without being given hemostatic agents, the group being given Feracrylum 1%, and the group being given Feracrylum 4%, each group consisting of 9 rats. Data were collected by calculating the bleeding time from the start of bleeding until the bleeding stopped after the gingival incision using a stopwatch and then recorded. Data analysis using Shapiro-Wilk, homogeneity test using Levene Test, nonparametric test using Kruskal-Wallis and Mann Whitney.Result: The results showed that the average bleeding time in the group without hemostatic agents, the group receiving 1% Feracrylum, and the group receiving Feracrylum 4% was 221 seconds, 103 seconds, and 50 seconds. The results of the Kruskal-Wallis and Mann Whitney showed that there was a significant difference in bleeding time between groups.Conclusion: The conclusion of this study is that the application of Feracrylum 4% was faster in stopping bleeding compared to the application of Feracrylum 1% after gingival incision in wistar rats.